MECHANISMS FOR USING THE NEW TEXTBOOKS IN THE PLANNING OF PEARLS ASSIGNMENTS (Conferencea, 2024)
Our article focuses on PIRLS assignments and plans through new textbooks. While reading this article, you will learn how to perform tasks based on the 4K model.